the Correlation Between Erythrocyte Index Levels with The Anemia Morphology in Leprosy Patients Before Therapy: A Secondary Data Research - Marrietta Sugiarti Sadeli; Luh Made Mas Rusyati; Ni Luh Putu Ratih Vibriyanti Karna (GLOBAL HEALTH SCIENCE GROUP, 2024)
Leprosy is a chronic inflammatory disease caused by Mycobacterium leprae. Chronic infection can cause anemia of chronic disease which is characterized by normochromic normocytic morphology. This study was conducted to assess the relationship between erythrocyte index levels (MCV, MCH, and MCHC) with the morphology of anemia that occurs in leprosy patients before treatment. A cross-sectional study using secondary data from medical records and management information system applications at Sanglah Hospital. The variables of this study were age, sex, hemoglobin levels, and erythrocyte index levels (MCV, MCH, and MCHC). Data were collected after permission was granted and ethical clearance was completed. Of the 156 study samples, 106 patients were diagnosed with leprosy who had not received therapy and 50 patients were not leprosy. The mean age of the patients was 39.15 ± 12.218 years and male patients were more common than female patients. There was a positive correlation between anemia, normal erythrocyte index levels, and the leprosy group. Following are the p-values, prevalence ratios, and confidence intervals; anemia [p= 0.017; PR(95% CI)= 1,458(1.034-2.056)], MCV, MCH, and MCHC [p= 0.020; PR(95% CI)= 1,268(1.010-1.591); p= 0.015; PR(95% CI)= 1,293(1,021-1,639); p= 0.009; PR(95% CI)= 1,297(1,036-1,624)]. The results of the analysis were statistically significant and clinically important. Leprosy patients had anemia before therapy with normochromic normocytic anemia morphology in accordance with anemia of chronic disease.